Uma nova geografia de ideias: diversidade de ações comunicativas para a dança - Martins, Giancarlo (2006)
In the last ten years, actions developed in dance, live and in the media, left the focus in Rio-São Paulo. Spread through several places in the country had taken a new geography of ideas that understand dance as a communication process of the body, organized as a thought that questions power structures, artistic procedures and boundaries between languages. This masters essay selects, as investigation corpus, some of these experiences employed in the education, in the circuit (festivals, shows and meetings), and in the research and creation in dance that, as survival strategy, creates decentralized cultural polar regions. The intend is to demonstrate that these experiences have propose new communication actions to dance. They push punctual changes in the dance market and in the development of public politics of cultural motivation and reconfigure, not only the esthetic system in which they are in, but the whole cultural system, contributing, in this way, for the dance survival and your effective insertion in the social fabric. As methodology, it was used a data analysis in a systematic way, that being, understanding the articulations between the investigated elements, based in the evolution theories proposed by the evolutionist scientist Richard Dawkins (2000-2001), in the concept of body and media proposed by the researchers Helena Katz and Christine Greiner (2000, 2001, 2003 and 2005) and in the cultural and political studies such as the ones developed by Bauman (1999), Agamben (2002), Bhabha (1998) and Foucault (1979 and 1996). Both, the bibliographic research and the field investigation (interviews and case studies) show that the strategies have been developed to recommend new ways of understanding and event organization, information flow and company conception and educational projects in dance. Actions that exist in the relation body and environment, in a contaminator flow, co evolutional, and non-determinist.